Endocytosis and Sorting of ErbB2 and the Site of Action of Cancer Therapeutics Trastuzumab and Geldanamycin - Cary D. Austin; Ann M. De Mazière; Paul I. Pisacane; Suzanne M. van Dijk; Charles Eigenbrot; Mark X. Sliwkowski; Judith Klumperman; Richard H. Scheller (2004)
ErbB2 is a transmembrane tyrosine kinase whose surface overexpression is linked to tumorigenesis and poor prognosis in breast cancer patients. Two models have emerged that account for the high surface distribution of ErbB2. In one model, the surface pool is dynamic and governed by a balance between endocytosis and recycling, whereas in the other it is retained, static, and excluded from endocytosis. These models have contrasting implications for how ErbB2 exerts its biological function and how cancer therapies might down-regulate surface ErbB2, such as the antibody trastuzumab (Herceptin) or the Hsp90 inhibitor geldanamycin. Little is known, however, about how these treatments affect ErbB2 endocytic trafficking. To investigate this issue, we examined breast carcinoma cells by immunofluorescence and quantitative immunoelectron microscopy and developed imaging and trafficking kinetics assays using cell surface fluorescence quenching. Surprisingly, trastuzumab does not influence ErbB2 distribution but instead recycles passively with internalized ErbB2. By contrast, geldanamycin down-regulates surface ErbB2 through improved degradative sorting in endosomes exclusively rather than through increased endocytosis. These results reveal substantial dynamism in the surface ErbB2 pool and clearly demonstrate the significance of endosomal sorting in the maintenance of ErbB2 surface distribution, a critical feature of its biological function.